Gastrointestinal stromal tumor of unusual phenotype after imatinib treatment: A case report and diagnostic utility of ETV1 mRNA in situ hybridization. Issue 49 (December 2017) - Jung, Minsun; Park, Sung-Hye; Jeon, Yoon Kyung; Won, Jae-Kyung; Yang, Han-Kwang; Kim, Woo Ho
Abstract: Rationale: Gastrointestinal stromal tumor (GIST) is the most common tumor of mesenchymal origin in gastrointestinal tract. Immunohistochemical (IHC) staining combined with a typical morphology is used for the diagnosis of GIST. Typically, IHC staining for v-kit Hardy–Zuckerman 4 feline sarcoma viral oncogene (KIT) and discovered on GIST-1(DOG1) is positive in almost all GISTs. However, imatinib mesylate, a specific inhibitor of KIT tyrosine kinase, frequently involves changes in the morphology and IHC staining of GIST, impeding the diagnosis. Recently, in situ hybridization (ISH) for E26 transformation-specific sequence variant 1 (ETV1) mRNA was introduced as a useful marker to diagnose GIST. Patient concerns: We report 2 cases of gastric GIST, which expressed unusual phenotypes after imatinib therapy. Diagnoses: The first patient was found to have a gastric subepithelial tumor in gastroduodenoscopy done for regular checkup. In biopsy of the tumor, it showed homogenous spindle cells that were positive to standard IHC markers for GIST. The second patient visited our hospital because of a palpable mass in the abdomen. In abdominal computed tomography (CT), a tumor arising from the stomach was found. A needle biopsy was done and the patient was diagnosed of gastric GIST because the biopsy showed spindle cells positive to typical IHC markers for GIST. After imatinib treatment, in both patients, the resected tumors were composed of heterogeneous spindle cells negative to KIT, DOG1, and CD34 IHC staining, which was unusual for GIST. However, ISH for ETV1 mRNA done for both biopsied and resected tumors was positive, even after imatinib treatment. A molecular analysis found a mutation in exon 11 of KIT gene before and after imatinib therapy in both patients, confirming the diagnosis of GIST. Interventions: Both patients took neoadjuvant imatinib treatment, and afterwards, underwent a surgical resection. Outcomes: The patients remain on imatinib treatment and no progression or recurrence has been detected to date. Lessons: ISH for ETV1 mRNA is a useful technique in diagnosing GIST when IHC with KIT, DOG1, or CD34 fail to stain positive after imatinib therapy. Abstract : Supplemental Digital Content is available in the text